Uncertainty and possibility - Akama, Yoko, author.
1 online resource
Keywords: Uncertainty and possibility are emerging as both theoretical concepts and fields of empirical investigation, as scholars and practitioners seek new creative, hopeful and speculative modes of understanding and intervening in a world of crisis.This book offers new perspectives on the central issues of uncertainty and possibility, and identifies new research methods which take advantage of disruptive and experimental techniques. Advancing a practical agenda for future making, it reveals how uncertainty can be engaged as a generative technology' for understanding, researching and intervening in the world. Drawing on key themes in creative methodologies, such as making, essaying, inhabiting and attuning, chapters explore contemporary sites of practice. The book looks at maker spaces and technology design, the imaginaries of architectural design, the temporalities of built cultural heritage, and interdisciplinary making and performing. Based on the authors' own academic work and their applied research with a range of different organizations, Uncertainty and Possibility outlines new opportunities for research and intervention. It is essential reading for students, scholars and practitioners in design anthropology and human-centred design.